Mouse models for dominant dystrophic epidermolysis bullosa carrying common human point mutations recapitulate the human disease - Smith, Blake; Nyström, Alexander; Nowell, Cameron J.; Haußer-Siller, Ingrid; Gretzmeier, Christine; Robertson, Susan J.; Varigos, George A.; Has, Cristina; Kern, Johannes S.; Pang, Ken C. (Disease models & mechanisms, 2021)
Heterozygous missense mutations in the human COL7A1 gene - coding for collagen VII - lead to the rare, dominantly inherited skin disorder dominant dystrophic epidermolysis bullosa (DDEB), which is characterised by skin fragility, blistering, scarring and nail dystrophy. To better understand the pathophysiology of DDEB and develop more effective treatments, suitable mouse models for DDEB are required but to date none have existed. We identified the two most common COL7A1 mutations in DDEB patients (p.G2034R and p.G2043R) and used CRISPR-Cas9 to introduce the corresponding mutations into mouse Col7a1 (p.G2028R and p.G2037R). Dominant inheritance of either of these two alleles results in a phenotype that closely resembles that seen in DDEB patients. Specifically, mice carrying these alleles show recurrent blistering that is first observed transiently around the mouth and paws in the early neonatal period and then again around the digits from 5-10 weeks of age. Histologically, the mice show micro-blistering and reduced collagen VII immunostaining. Biochemically, collagen VII from these mice displays reduced thermal stability, which we also observed to be the case for DDEB patients carrying the analogous mutations. Unlike previous rodent models of epidermolysis bullosa, which frequently show early lethality and severe disease, these mouse models, which to our knowledge are the first for DDEB, show no reduction in growth and survival, and - together with a relatively mild phenotype - represent a practically and ethically tractable tool for better understanding and treating epidermolysis bullosa.This article has an associated First Person interview with the first author of the paper.
Gesehen am 07.07.2022